Abatement of the dysfunctional hypothalamic–pituitary–gonadal axis due to ciprofloxacin administration by selenium in male rats (2021)
The present study examined the influence of selenium on ciprofloxacin‐mediated reproductive dysfunction in rats. The research design consisted of five groups of eight animals each. The rats were administered 135 mg/kg body weight of ciprofloxacin per se or simultaneously with selenium at 0.25 and 0.5 mg/kg for 15 uninterrupted days. Antioxidant and inflammatory indices were assayed using the testes, epididymis, and hypothalamus of the animals after sacrifice. Results revealed that ciprofloxacin treatment per se interfered with the reproductive axis as demonstrated by diminished serum hormonal levels, sperm quality, and enzymatic indices of testicular function, which were, however, abrogated following selenium co‐treatment. Besides this, administration of selenium attenuated the depletion of glutathione level, inhibition of catalase, superoxide dismutase, glutathione‐Stransferase and glutathione peroxidase activities with a concomitant reduction in reactive oxygen and nitrogen species, and lipid peroxidation in ciprofloxacintreated in rats. Selenium treatment also mitigated ciprofloxacin‐mediated elevation in nitric oxide level and of myeloperoxidase activity as well as histological lesions in the animals. Overall, selenium attenuated impairment in the male reproductive axis due to ciprofloxacin treatment through abatement of inflammation and oxidative stress in rats.